Feasibility of FDCT Early Brain Parenchymal Blood Volume Maps in Predicting Short-Term Prognosis in Patients With Aneurysmal Subarachnoid Hemorrhage - Wen, Lili; Zhou, Longjiang; Wu, Qi; Zhou, Xiaoming; Zhang, Xin (Frontiers in Neurology, 2022)
Purpose: Aneurysmal SAH is generally accompanied with cerebral perfusion changes. We aim to measure the parenchymal blood volume (PBV) maps acquired by C-arm flat-panel detector CT (FDCT) to assess the cerebral blood volume at early stage in aneurysmal SAH and to explore the correlation with the outcomes at discharge. Methods: Data of 66 patients with aneurysmal SAH who underwent FDCT PBV examination were retrospectively analyzed. The PBV of regions-of-interest including the cortices of bilateral frontal lobe, parietal lobe, occipital lobe and cerebral hemisphere as well as the basal ganglia were measured and quantitatively analyzed. The clinical and imaging data of the patients were also collected, and logistic regression analysis was performed to explore the correlation between the perfusion parameters and outcomes at discharge. Results: The favorable and poor outcome at discharge were found in 37 (56.06%) and 29 (43.94%) patients, respectively. Whole brain PBV were significantly correlated with the Hunt-Hess grades ( p<0.005) and WFNSS grades ( p<0.005). The whole brain PBV of the poor prognosis was significantly higher than that of the favorable prognosis (35.17±7.66 VS 29.78±5.54, p<0.005). Logistic regression analysis showed the PBV of parietal lobe at bleeding side (OR=1.10, 95%CI: 1.00- 1.20, p=0.04) was an independent risk factor predicting the short-term prognosis. Conclusions: PBV maps could reflect the cerebral blood volume at early stage in aneurysmal SAH. It enables a one-stop imaging evaluation and treatment in the same angio suite, and may serve as a reliable technique in clinical assessing aneurysmal SAH.